2021
DOI: 10.3390/reactions2030018
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Hydrogen Storage Properties of the Multiphase Ti0.3V0.3Mn0.2Fe0.1Ni0.1 Alloy

Abstract: The hydrogen storage properties of a multi-component alloy of composition Ti0.3V0.3Mn0.2Fe0.1Ni0.1 were investigated. The alloy was synthesized by arc melting and mechanical alloying, resulting in different microstructures. It was found that the as-cast alloy is multiphase, with a main C14 Laves phase matrix along with a BCC phase and a small amount of Ti2Fe-type phase. The maximum hydrogen storage capacity of the alloy was 1.6 wt.%. We found that the air-exposed samples had the same capacity as the as-cast sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Other important methods include electrochemical deposition, template-assisted synthesis, in-situ growth methods, vacuum induction, plasma-metal reaction, and electric arc melting methods. [147][148][149][150][151][152] The multiphase material consisting of CaÀ NiÀ Cu alloy with a composition of 30 % Ca, 50 % Ni, and 20 % Cu was prepared by Anshul and Mohammad [148] using the vacuum induction melting method. The alloy formed is brittle and can be easily crushed to powder and activated in situ.…”
Section: Design Synthesis and Mechanism Of Multiphase Materials In Hy...mentioning
confidence: 99%
See 1 more Smart Citation
“…Other important methods include electrochemical deposition, template-assisted synthesis, in-situ growth methods, vacuum induction, plasma-metal reaction, and electric arc melting methods. [147][148][149][150][151][152] The multiphase material consisting of CaÀ NiÀ Cu alloy with a composition of 30 % Ca, 50 % Ni, and 20 % Cu was prepared by Anshul and Mohammad [148] using the vacuum induction melting method. The alloy formed is brittle and can be easily crushed to powder and activated in situ.…”
Section: Design Synthesis and Mechanism Of Multiphase Materials In Hy...mentioning
confidence: 99%
“…Some common methods used in the synthesis of multiphase materials for hydrogen storage are co‐precipitation, sol‐gel process, mechanical alloying, chemical vapor deposition, and hydrothermal synthesis. Other important methods include electrochemical deposition, template‐assisted synthesis, in‐situ growth methods, vacuum induction, plasma‐metal reaction, and electric arc melting methods [147–152] …”
Section: Adsorption/desorption Using Metal‐doped Materials: Effect Of...mentioning
confidence: 99%
“…On the other hand, intermetallic Laves C14 alloys usually absorb 1 H/M forming monohydrides maintaining the C14 structure type with expanded lattice parameters [11,12,23]. Studies on hydrogen storage properties in multi-phase multicomponent alloys have also been reported [32,33]. Recently, Sleiman et al [32] studied the microstructure and hydrogen storage properties of the multi-phase Ti0.3V0.3Mn0.2Fe0.1Ni0.1 alloy.…”
mentioning
confidence: 99%
“…Studies on hydrogen storage properties in multi-phase multicomponent alloys have also been reported [32,33]. Recently, Sleiman et al [32] studied the microstructure and hydrogen storage properties of the multi-phase Ti0.3V0.3Mn0.2Fe0.1Ni0.1 alloy. The authors reported the alloy presented a microstructure mainly composed of C14 Laves phase with a minor amount of BCC phase (around 10%).…”
mentioning
confidence: 99%
“…This Special Issue on "Hydrogen production and storage" covers both production and storage in a balanced way and contains six articles, one review, and one viewpoint. Among the six articles, three are dedicated to solid materials for the hydrogen storage: the first one concerns a multiphase Ti 0.3 V 0.3 Mn 0.2 Fe 0.1 Ni 0.1 alloy synthesized by arc melting and showing a maximum hydrogen storage capacity of 1.6 wt% [1]; another one concerns sodium alanate, NaBH 4 , with its 7.4 wt% H 2 , for which the effect of nanoconfinement on the hydrogen release processes was thoroughly studied [2]. The last was on activated carbons, evaluated for their capacity to adsorb hydrogen.…”
mentioning
confidence: 99%